2018
DOI: 10.1111/resp.13437
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of mutations of cystic fibrosis in the 22 Arab countries: A systematic review

Abstract: Cystic fibrosis (CF) is an autosomal recessive genetic disease caused by mutations in the CFTR gene, with various clinical manifestations that affect pulmonary, digestive, exocrine and male reproductive functions as well as the bones and kidneys. This study aimed to reveal the spectrum of CFTR gene mutations in Arab CF patients and their corresponding clinical phenotypes among the 22 Arab countries. We searched four literature databases (PubMed, Science Direct, Web of Science and Scopus) from their times of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 82 publications
1
26
0
Order By: Relevance
“…Beyond variability in carrier frequency, the wide range observed in incidence may be in part explained by under-diagnosis and under-reporting of cases [75,76]. The incidence of CF in Asia may therefore be under-estimated.…”
Section: Asiamentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond variability in carrier frequency, the wide range observed in incidence may be in part explained by under-diagnosis and under-reporting of cases [75,76]. The incidence of CF in Asia may therefore be under-estimated.…”
Section: Asiamentioning
confidence: 99%
“…In Arab countries, the major challenges are to improve the diagnosis and the detection of mutations before irreversible organ damage has developed and to promote the constitution of national registries [75,76], which will help to improve CF management and health policy planning. To the best of our knowledge, no CF NBS program is implemented to date in the Arab world, but CF NBS is promoted by the annual meeting for NBS in the Middle East and North Africa.…”
Section: Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…The monumental interest of the triple-combination is that a large proportion of patients with CF are eligible for treatment in numerous populations. However, in specific ethnic groups, F508del is absent (such as Iraq, Sudan, Qatar, Japan and China) or extremely rare (Jordan 6%–7%, Bahrain 8%) [ 37 ] ( Table S1 ). The challenge is thus to make personalized therapy accessible to all patients.…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…In a recent publication in Respirology , Al‐Sadeq et al . present a commendable systematic review of the spectrum of CF mutations in the 22 Arab countries . Seventy‐two studies were identified that document disease in 5481 patients and 45 families, in whom a total of 115 mutations were recognized.…”
mentioning
confidence: 99%